What Does It All Mean? A Humanistic Account of Human Experience. - Adams, William A. (Luton : Andrews UK, 2013)
As a young man Bill Adams travelled the world teaching US citizens abroad on behalf of a large state university on the East Coast. Back home he reflected that if there were answers to the great questions of life, then he'd not found them - not in India, in Europe, in China, or Japan. In time he came to see that his lifelong interest in how the mind works could be the clue to the meaning of life. Socrates had been right all along: Know thyself. Adams now sets out a new reasoned argument, base...
Cover; Contents; Front matter; Title page; Copyright page; Acknowledgments; Preface; Body matter; 1: The Meaning of Life; 2: The Human Point of View; 3: Invisible Assumptions; 4: Bipolar Consciousness; 5: Finding the Telos; 6: Psychological Projection; 7: Projective Agency; 8: Intersubjectivity; 9: What About God?; 10: Questions and Answers; 11: How Do I Know?; 12: Methods of Inquiry; Back matter; References; Also available
Description based upon print version of record.
Keywords: Meaning (Psychology); Psychology; PSYCHOLOGY / Reference; Electronic books